Analysis of liquid materials in low vacuum with Wet‐SIMS. (22nd May 2014) - Seki, Toshio; Fujii, Makiko; Kusakari, Masakazu; Nakagawa, Shunichiro; Aoki, Takaaki; Matsuo, Jiro; Yurimoto, Hisayoshi
<x xml:space="preserve">Abstract</x> In conventional SIMS with keV‐energy ion beams, elastic collisions occur between projectiles and atoms in the constituent molecules. The collisions produce fragments, making the acquisition of molecular information difficult. Volatile liquid samples (wet samples) are also difficult to measure using conventional SIMS because samples must be dried first and then introduced into the high‐vacuum chamber. In contrast, ion beams with MeV‐energy excite electrons near the surface and enhance the ionization of high‐mass molecules; hence, a fragment‐suppressed SIMS spectrum of ionized molecules can be obtained. We developed a SIMS analysis system for wet samples (Wet‐SIMS) that works under low‐vacuum pressures up to 1000 Pa using heavy MeV‐energy ion beams. The evaporation of heptanoic acid was suppressed under the low‐vacuum pressure of 1000 Pa, and the wet samples, which included volatile materials with different vapor pressures, could be measured using heavy MeV‐energy ions. Copyright © 2014 John Wiley & Sons, Ltd.